Pengaruh Motivasi, Disiplin Kerja dan Lingkungan Kerja terhadap Kinerja Guru: Narrative Literature Review - Putri, Dwiayu Nabila; Azahra, Arinka Dwi (Journal of Information Systems and Management (JISMA), 2024)
Abstract - The purpose of writing this article is to analyze the influence of motivation, work discipline and work environment on teacher performance on 3 (three) articles. This narrative literature review aims to identify and summarize previously published articles without any criticism for the articles reviewed. The type of research used in these 3 articles is quantitative research. Teachers are the spearhead in improving the quality of education, especially in providing motivation to students so as to improve the quality of education. Work discipline is one of the factors that affect teacher performance. Thus schools that in the teaching and learning process grow discipline will function as a shaper of individual values and norms, self-mastery, attitudes and responsibilities for a teacher. A comfortable environment causes the level of teacher concentration in teaching to increase and these conditions can increase productivity.